Flesh-coloured tights in space: Intersections of spectacular corporeality and visuality in The Seven Sisters. Issue 3 (1st December 2016) - Singer, Elyse
This article examines the intersections between female performing bodies and stage spectacle in The Seven Sisters, Laura Keene's 1860 musical extravaganza. In its consideration of patriotic tableaux, precision dance numbers, and the grand transformation scene, the essay suggests relationships between visuality, corporeality and aesthetics at a significant turning point in the development of American popular culture that overlapped with the Civil War. The article argues that contemporary media theories may provide a lens for looking at different historical body-to-spatial models featuring nascent American chorus girls, and locates moments of affect and subjectivity on the part of the performers.